2017
DOI: 10.3233/bmr-160571
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain prevalence in healthcare professionals and identification of factors affecting low back pain

Abstract: Considering that head-neck and trunk postures are changeable factors that are among the factors affecting LBP, correcting the working posture gains importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
2
24
1
2
Order By: Relevance
“…Pain in the elbow was found to be the least reported complaint (11.97%), and this almost matches with the order of complaints as reported by participants in other studies [3,6]. By observing these numbers and frequencies, we found that low back pain among all is the most frequent complaint that we need to pay special attention to; this MSC has been already studied separately and the results were almost similar to the one we found (70.09%) [19]. This has urged us to propose that healthcare organizations should pay special attention to low back pain.…”
Section: Discussionsupporting
confidence: 88%
“…Pain in the elbow was found to be the least reported complaint (11.97%), and this almost matches with the order of complaints as reported by participants in other studies [3,6]. By observing these numbers and frequencies, we found that low back pain among all is the most frequent complaint that we need to pay special attention to; this MSC has been already studied separately and the results were almost similar to the one we found (70.09%) [19]. This has urged us to propose that healthcare organizations should pay special attention to low back pain.…”
Section: Discussionsupporting
confidence: 88%
“…The DJS questionnaire used in this study included six items representing the stress of the Korean dentists selected through the pilot survey. Because practicing dentists work in a position with their necks, shoulders and backs bent for long periods of time, they are prone to neck, shoulder, back, wrist and finger pain. It is believed that fatigue due to physical stress and pain leads to mental and emotional job stress.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders (MSDs) are prevalent in working populations around the globe [16]. Long-term and severe MSDs could affect quality of life, reduce work productivity, increase sick leave absence, shorten working life and cause chronic occupational disability and constitute a major health challenge for individuals and healthcare systems around the world [5, 7, 8].…”
Section: Introductionmentioning
confidence: 99%